Heterogeneity in tumours: Validating the use of radiomic features on 18F-FDG PET/CT scans of lung cancer patients as a prognostic tool. (March 2020) - Krarup, Marie Manon Krebs; Nygård, Lotte; Vogelius, Ivan Richter; Andersen, Flemming Littrup; Cook, Gary; Goh, Vicky; Fischer, Barbara Malene
Highlights: PET-based radiomic features (RFs) may be able to predict survival. Initial radiomic studies on lung cancer patients show promising results. Validation of RFs on external patients cohorts is necessary. GTV and clinical stage predicted progression free survival (PFS). None of the preselected RFs predicted independently for PFS. Abstract: Aim: The aim was to validate promising radiomic features (RFs) 1 on 18 F-flourodeoxyglucose positron emission tomography/computed tomography-scans ( 18 F-FDG PET/CT) of non-small cell lung cancer (NSCLC) patients undergoing definitive chemo-radiotherapy. Methods: 18 F-FDG PET/CT scans performed for radiotherapy (RT) planning were retrieved. Auto-segmentation with visual adaption was used to define the primary tumour on PET images. Six pre-selected prognostic and reproducible PET texture -and shape-features were calculated using texture respectively shape analysis. The correlation between these RFs and metabolic active tumour volume (MTV) 3, gross tumour volume (GTV) 4 and maximum and mean of standardized uptake value (SUV) 5 was tested with a Spearman's Rank test. The prognostic value of RFs was tested in a univariate cox regression analysis and a multivariate cox regression analysis with GTV, clinical stage and histology. P -value ≤ 0.05 were considered significant. Results: Image analysis was performed for 233 patients: 145 males and 88 females, mean age of 65.7 and clinical stage II-IV. Mean GTV was 129.87 cm 3 (SD 130.30 cm 3 ). Texture and shape-features correlated more strongly to MTV and GTV compared to SUV-measurements. Four RFs predicted PFS in the univariate analysis. No RFs predicted PFS in the multivariate analysis, whereas GTV and clinical stage predicted PFS ( p = 0.001 and p = 0.008 respectively). Conclusion: The pre-selected RFs were insignificant in predicting PFS in combination with GTV, clinical stage and histology. These results might be due to variations in technical parameters. However, it is relevant to question whether RFs are stable enough to provide clinically useful information.